PENERAPAN STANDAR OPERASIONAL PROSEDUR FOOD AND BEVERAGE SERVICE DI HOTEL SWISS BELCOURT KUPANG - Christina Mantolas; Yudha Eka Nugraha; Feny Susana Eky; Martarida Bagaihing (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2022)
Standard Operating Procedure is a guideline or reference for carrying out work tasks in accordance with the functions and tools for assessing the performance of government agencies based on technical, administrative and procedural indicators in accordance with work procedures, work procedures and work systems in the work unit concerned. The objective of this study is to understand how to implement standard operating procedures for food and beverage service at the swiss Belcourt Kupang hotel. The research is presented qualitatively. Based on the results obtained, the implementation of standard operating procedures (SOP) for food and beverage service at the Swiss Belcourt Kupang Hotel is very important for waiters to be applied, especially in providing food and beverage services so as to make the work more directed and optimal. The conclusion is that the implementation of the Operational Standard Procedure (SOP) has not gone well, food and beverage service employees have not implemented SOPs regularly, the knowledge menu of a waiter/waitress has not been developed properly, the lack of employees so that it affects the smooth running of the service.